Effect of Flow Disturbance Geometry on Thermal Hydraulic Performance of Forced Air-Cooled Heat Sinks for CPU Cooling - Annisa Fitriola Suryawati; Damora Rhakasywi; Nicky Yongkimandalan; Bima Rakha Adhitama (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2026)
The increasing thermal load in modern electronic devices necessitates efficient and reliable cooling strategies, particularly for air-cooled heat sinks in CPU applications. This study numerically investigates the effect of flow-disturbance geometry on the thermal–hydraulic performance of a forced air-cooled channel under constant heat flux. Three configurations—circular, square, and octagonal—were evaluated against a baseline using a validated CFD approach based on the RANS equations with the k–ω SST model, with a 7.65% deviation. The results show that geometric disturbances significantly influence temperature distribution and pressure drop. The octagonal model achieves the lowest excess temperature across airflow velocities of 1–2 m/s but produces the highest pressure drop, while the square model provides notable temperature reduction with moderate pressure loss by improving airflow uniformity and disrupting the thermal boundary layer. Overall, the square configuration offers the most optimal balance between heat transfer and energy efficiency.